PREDICTING FINANCIAL DISTRESS USING ALTMAN SCORE, GROVER SCORE, SPRINGATE SCORE, ZMIJEWSKI SCORE (CASE STUDY ON CONSUMER GOODS COMPANY) - Hantono, Hantono (Universitas Sam Ratulangi, 2019)
This study aims to detect the financial distress on consumer goods companies listing on the Indonesia Stock Exchange 2013-2017 by using altman score, grover score, springate score, zmijewski score.The object of this study is all consumer goods companies listing on the Indonesia Stock Exchange which publishes audited financial statements for fiscal year 2013 - 2017, which amounted to 24 (twenty four) companies. The sampling technique is by using purposive sampling method where the sample is determined based on certain criteria determined by the researcher and has limitations in terms of generalization. The sample of research is 42 (fourty two companies) Data collection method using documentation method Data analysis technique used is descriptive qualitative analysis using altman score, grover score, springate score, zmijewski score..